CLOUD REMOVAL MENGGUNAKAN CITRA LANDSAT - Andrean, Lius (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Cloud Removal is used to remove or reduce the clouds on the digital image which is taken from Landsat Satellite and to search the missing value which is covered by clouds. The purpose of this research is to find out information about the data which are contained in the missing value and also to determine the level of success of Wavelet Haar, Measure Of Center, and Image Averaging which are used to remove the cloud. Based on the process to reduce the error, Wavelet Haar method is the fastest one, because it is only requires one image as comparison. In other hand, Measure Of Center and Image Averaging methods require minimum 4(four) images to be the reference image. The experimental result shows that Wavelet Haar, Measure Of Center and Image Averaging method can reduce the error value of the cloud. Image Averaging method is the best method because it can reduce the error value from 21,55% become 13,77%. Key words Cloud Removal, Wavelet Haar, Measure Of Center, Image Averaging